2021
DOI: 10.3390/nu13093136
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Vitamins and Their Prevalence in Fortified Food and Supplements in Japan

Abstract: Most vitamins are primarily ingested from foods. However, it has been reported that intakes of some vitamins do not meet the nutrition reference values even in high-income countries. In this case, vitamin-fortified foods and/or vitamin supplements are helpful to fix insufficient/deficient status. However, it is not clear whether consumers are aware of their nutritional status or whether they use these products efficiently. To address this issue, we conducted an online cross-sectional questionnaire survey among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Then, we asked the participants who answered "rarely" why they could not follow a well-balanced diet; 41.5% of the participants answered "I have no time to spare", and 36.3% of them answered "I do not have enough money". This result is almost the same as that of the previous study [19].…”
Section: Well-balanced Dietsupporting
confidence: 91%
See 3 more Smart Citations
“…Then, we asked the participants who answered "rarely" why they could not follow a well-balanced diet; 41.5% of the participants answered "I have no time to spare", and 36.3% of them answered "I do not have enough money". This result is almost the same as that of the previous study [19].…”
Section: Well-balanced Dietsupporting
confidence: 91%
“…In addition, a well-balanced diet is also encouraged to prevent COVID-19 [21,22]. However, only one-third of participants consumed a well-balanced diet almost every day in this study, and this result is almost the same as that of our previous study (33.2%) [19]. The major reasons why participants could not consume a well-balanced diet were time and money.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…The Consumer Affairs Agency in Japan has cautioned on these dietary supplements several times [ 17 ]. However, we reported that some Japanese consumers use fortified foods and dietary supplements not only to supplement their nutrient intake, but also to prevent infectious diseases [ 18 ]. Therefore, we conducted an online cross-sectional questionnaire survey to clarify the prevalence of the use of dietary supplements to prevent SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 99%